Time analysis for the IAAF World Championships London 2017 steeplechase women's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The women`s steeplechase final took place on August 11th on a relatively cool evening. Coburn`s winning time of 9:02.58 was a Championship Record with her US compatriot and silver medallist Frerichs also achieving a personal best time; it was the first 1-2 finish for the USA in a global final of a distance event since 1912. The two Americans approached the final water jump level with Jepkemoi but their superior approach and clearance gave them an advantage entering the home straight that they maintained to the finish. Chepkoech, who finished fourth, made the highly unusual mistake of forgetting to cut in off the regular 400 m track to take the water jump on the second lap, and lost valuable time in retracing her steps to cross it. Further down the finishing places, Yavi also ran a personal best time, as did Casetta (a South American Area Record) and Lalonde (a Canadian record). The results for all finishers are shown. (Attention! registration on the IAAF site is required for downloading)